Pendidikan Jiwa Perspektif Ibnu Qayyim - Fani, Farid Al; Aziz, Nur; Rohimah, Siti (TSAQOFAH, 2025)
Spiritual education is a fundamental aspect in the formation of a complete human being, yet it is often overlooked in modern educational systems that prioritize cognitive development and technical skills. From an Islamic perspective, education encompasses intellectual, spiritual, and moral dimensions in an integrated manner. This paper aims to examine the concept of spiritual education (tarbiyah al-nafs) according to Ibn Qayyim al-Jawziyyah, a prominent 14th-century scholar known for his contributions to tazkiyatun nafs (purification of the soul). The study is conducted through a literature review of Ibn Qayyim's major works alongside contemporary references on Islamic education. The findings reveal that the objective of soul education according to Ibn Qayyim is to cultivate individuals with purified souls, strong spirituality, and noble character. The methods proposed include tazkiyah (purification), riyadhah (spiritual discipline), taubah (repentance), and the reinforcement of spiritually nurturing environments as means for internalizing values. This concept is highly relevant in addressing the moral and spiritual crises faced by contemporary education. The study concludes that Ibn Qayyim’s approach to soul education holds strategic significance in shaping learners who are not only intellectually capable but also morally grounded and spiritually resilient.